Sleep timing in flies from “adolescence” to adulthood - Esther D. Domenie; Paola Cusumano; Sara Montagnese; Rodolfo Costa (Fly)
The aim of the present study was to assess sleep timing in Drosophila melanogaster at different ages, within the setting of an enforced schedule of varying light-dark stimuli, simulating light exposure variations between four typical office working days and one free day spent outside by a human, for a total of 30 days. Locomotor activity recording started when male flies were 3 days old. Flies exhibited a bimodal activity pattern, with a morning and an evening peak, and clear anticipation of the lights on and lights off transitions. From experimental day 10 (i.e. 12-day-old flies) onwards, a decrease in activity counts/increase in sleep amount were observed. On free days, a rise in activity counts and a reduction in sleep amount during the lights on interval was observed and was also present, albeit less obvious, on the subsequent working day during the lights off interval. A progressive delay in sleep onset was observed in the first days of the experiment, peaking on day 4 (i.e. 6-day-old flies), after which sleep onset timing gradually advanced. A delay in sleep offset was also observed for the first 13 days of the experiment, after which sleep offset stabilized. In conclusion, ‘adolescent’ flies exhibited changes in sleep timing that were reminiscent of those of human adolescents.